Sumbangan Dana Kampanye Pemilu dan Kejahatan Korporasi - arief amrullah (Fakultas Hukum Universitas Islam Indonesia, 2004)
The fonn of corporate crime is not only in the field of environment pollution, deceive of consummer, unfair trade practices, etc, but also in the field ofpolitics. In this field, it is usually for economic advantage through the campaign fund contributed to the party. In USA, Watergate scandal, for example, its hows the corporate involvement in the general ellections arena, so that in 1971 the USA government legislated a new regulation limiting the sum ofcorporate contribution to political party. lndonesia, in the face ofgenertal election 2004, has anticipated it by UU No. 12 Tahun 2003. However, if we pay close attention to penal policy as regulated in Article 138 section (5) which justregulates capital punishment (imprisonment and fine), while the additional punishment is not regulated in thatstatute, it is, worried that the statute will not be efective to prevent the corporation's violation of the constribution limit tolerated by the statute the weakness of the fonmulation policy will Influence the interaction perpetuation which benefit each-otherbetween contributor and receiver of contribution. As a consequence, it is difficult to prevent the conspirative connection for each elite group interest Key words: Campaign contribution,corporate crime.